Transmission of 96 Gbps Over 50-m GI-POF Using 6 CWDM Channels in S, C, and L Optical Bands - Hossam A. I. Selmy; Gil M. Fernandes; Rogerio Nogueira; Ricardo Oliveira (IEEE Access)
An aggregate transmission of 96 Gbps over 50 m of graded index plastic optical fiber (GI-POF) is demonstrated using six coarse wavelength multiplexing (CWDM) channels in S, C and L optical bands. Each channel transmits an equal rate of 16 Gbps with NRZ formats. The used CWDM channels are 1490 and 1510 in the S band, 1530 and 1550 in the C band, and 1570 and 1590 in the L band. In addition, 16, 14 and 12 Gbps were tested at varying levels of optical power for each CWDM channel, and the BER levels were measured for 50 m GI-POF transmission and compared to that of back-to-back transmission.